Cutaneous Metastasis of Pulmonary Adenocarcinoma - Katherine B. Oakley; Anneli R. Bowen; Lauren M. Madigan (Annals of Internal Medicine: Clinical Cases)
Lung cancer remains a leading cause of malignancy-related mortality among adults worldwide. Metastasis of primary lung adenocarcinoma to the skin is rare, morphologically heterogeneous, and may affect any body site. Cutaneous metastases portend a poor prognosis with worsened survival rates. The diagnosis is typically established via histopathology with supportive immunohistochemistry. Treatment varies based on the extent of involvement.